Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1007/s11266-018-0017-8
|View full text |Cite
|
Sign up to set email alerts
|

“Charity Begins at Home”: Informal Caring Barriers to Formal Volunteering Among Older People

Abstract: Formal volunteering is an important economic and social activity. In many countries, prevalence of volunteering is decreasing overall, including among older people who constitute a major volunteering resource. This qualitative study explored reasons for nonvolunteering among seniors, with a focus on those who attribute their non-volunteering to their existing helping commitments. Forty-nine Australian interviewees aged 60+ years described a range of social, psychological, and temporal factors that resulted in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 73 publications
(77 reference statements)
1
13
0
Order By: Relevance
“…Other studies have indicated that people with less socio-political capital were less likely to volunteer (Li et al ., 2010; Parkinson et al ., 2010). People who lack confidence and interest, are self-ageist or feel excluded also declined to volunteer (Cocca-Bates and Neal-Boylan, 2011; Pettigrew et al ., 2018; Withall et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have indicated that people with less socio-political capital were less likely to volunteer (Li et al ., 2010; Parkinson et al ., 2010). People who lack confidence and interest, are self-ageist or feel excluded also declined to volunteer (Cocca-Bates and Neal-Boylan, 2011; Pettigrew et al ., 2018; Withall et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Older adults who need to balance their time between care-giving and work responsibilities (Myers et al ., 2013) were unable to commit sufficient time to volunteering (Lee et al ., 2008; Resnick et al ., 2013; Serrat et al ., 2017). Some older adults prioritised the intermediate network centred on family members and preferred informal volunteering such as care-giving for their family (Dávila, 2018; Pettigrew et al ., 2018).…”
Section: Resultsmentioning
confidence: 99%
“…Programs providing older adults with the opportunity to trial volunteering may therefore be useful in improving perceptions of the attractiveness and feasibility of this activity, thereby potentially increasing volunteering prevalence rates among this group. It is important to recognize, however, that engagement in volunteering may not be feasible or desirable for all older adults, especially those suffering from illness or disability or who provide substantial levels of care to family and friends (Pettigrew et al, 2018). Recognizing the legitimacy of informal volunteering and valuing the contribution of older adults who engage in these activities is important to ensuring efforts to recruit older adults into formal volunteering do not result in undue stress.…”
Section: Discussionmentioning
confidence: 99%
“…Given previous research has partially attributed reluctance to participate in volunteering among older adults to a "misguided sense of what volunteering encompasses" (Warburton, Paynter, & Petriwskyj, 2007), the approach of encouraging trial to change attitudes may assist in overcoming this barrier. In addition, older adults have been found to be concerned about taking on formal volunteering commitments for fear of being "tied down" or needing to renege on their volunteering responsibilities due to personal or family issues (Pettigrew, Jongenelis, Jackson, & Newton, 2018;Warburton et al, 2007;Warburton et al, 2001). They can also believe they are "too old" and lack confidence in their ability to contribute to society (Warburton et al, 2007;Warburton et al, 2001).…”
mentioning
confidence: 99%
“…Especially in recent years, a shift to more flexible, project-based forms of volunteer work has been pursued (McLennan, Whittaker, & Handmer, 2016), which may also support ways of coping with and mobilising sufficient human capital for the pandemic's current and upcoming challenges. The baby boomer generation, including the large birth cohorts from 1955 to 1969, has begun to demonstrate its tremendous potential for the volunteer sector as its members have started to retire (Hansen & Slagsvold, 2020;Pettigrew et al, 2019). In fact, because volunteer work presents the opportunity to enhance healthy ageing (Carr & Hendricks, 2011;Jongenelis et al, 2019;Niebuur et al, 2018;Pavelek, 2013), retirees can benefit from a 1 In Austria, baby boomers are defined as members of the generation born from 1955 to 1969 (Meier, 2019;Wanka, 2019).…”
Section: Introductionmentioning
confidence: 99%